Approaching Navigational Cues of Web Documents from Relevance Theory and Genre Theory - Zhang, Lei (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2013)
Based on Relevance Theory proposed by Sperber and Wilson, this research explores genres at multiple levels and its influence on expectations of relevance in interpreting the space particular details occur and in comprehending particular details, and navigation patterns directed by expectations of relevance. It proposes a conceptual model of genre-assisted… Basée sur la théorie de la pertinence proposée par Sperber et Wilson, cette recherche explore les genres à de multiples niveaux et leur influence sur les attentes touchant la pertinence dans l’interprétation des détails particuliers de l’espace, et des modèles de navigation basés sur…